Integrated traditional Chinese and western medicine nursing bundles for a patient undergoing percutaneous coronary intervention for acute myocardial infarction (1例急性心肌梗死患者经皮冠状动脉介入治疗术后中西医结合集束化护理) - CHANG Yu (常瑜); HUANG Yanping (黄砚萍) (Association of Integrative Nursing, 2024)
This paper summarized the integrated traditional Chinese and western medicine nursing bundles for a patient undergoing percutaneous coronary intervention for acute myocardial infarction. The basic nursing plan was formulated based on a comprehensive nursing risk assessment. Integrated traditional Chinese and western medicine nursing bundles included monitoring of vital signs, postoperative health education, intra-aortic ballon pump-associated catheter maintenance, skin care, Psycho-Cardiology care and interventions on sleep quality, abdominal distension, chest tightness and difficulty breathing syndrome. The integrated traditional Chinese and western medicine nursing bundles are effective to relieve the symptoms, reduce the postoperative complications and improve the prognosis and quality of life of the patient undergoing percutaneous coronary intervention for acute myocardial infarction. (本文总结1例急性心肌梗死患者经皮冠状动脉介入治疗术后中西医结合集束化护理体会。在完善护理评估的基础上, 制定基础护理方案。在密切监测病情的基础上, 实施集束化护理措施, 包括术后健康宣教、主动脉内球囊反搏(IABP)管路护理、皮肤护理、双心护理、睡眠护理, 以及针对腹胀、胸闷憋喘症状的干预等, 旨在有效缓解症状, 减少并发症、后遗症等的发生, 改善预后和患者生活质量。)